2013
DOI: 10.3319/tao.2012.12.06.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Seasonal Variations of Sea-Air CO2 Fluxes in the Northern East China Sea

Abstract: Temperature, salinity, chlorophyll a (Chl-a), nitrate, and sea-air differences of CO 2 partial pressure (ΔpCO 2 ) were extensively investigated in the northern East China Sea (ECS) during seven research cruises from 2003 to 2009. The ΔpCO 2 showed large intraseasonal variation in the spring and summer. In spring, the areal mean ΔpCO 2 in May 2004 was almost half of that in April 2008, probably associated with differences in sea surface temperature (SST). In summer, the areal mean ΔpCO 2 in August 2003 was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…The annual CO 2 uptake rate in this study area was considerably larger than the estimate for worldwide continental shelves (-1.1 mol m -2 yr -1 ; Chen and Borges 2009) and the global mean (-0.51 mol m -2 yr -1 ; Takahashi et al 2009). Kim et al (2012) reported that the annual sea-air CO 2 flux in the northern East China Sea was -2.2 ± 2.1 mol m -2 yr -1 , which is comparable to our result. Therefore, the Ulleung Basin of the East Sea, like the East China Sea, acts as a strong sink of atmospheric CO 2 .…”
Section: Factors Influencing the Seasonal Variability Of Surface Fcosupporting
confidence: 91%
See 1 more Smart Citation
“…The annual CO 2 uptake rate in this study area was considerably larger than the estimate for worldwide continental shelves (-1.1 mol m -2 yr -1 ; Chen and Borges 2009) and the global mean (-0.51 mol m -2 yr -1 ; Takahashi et al 2009). Kim et al (2012) reported that the annual sea-air CO 2 flux in the northern East China Sea was -2.2 ± 2.1 mol m -2 yr -1 , which is comparable to our result. Therefore, the Ulleung Basin of the East Sea, like the East China Sea, acts as a strong sink of atmospheric CO 2 .…”
Section: Factors Influencing the Seasonal Variability Of Surface Fcosupporting
confidence: 91%
“…The Tsushima Warm Current branched from the Kuroshio Current and passed through the East China Sea before entering the study area. Kim et al (2012) measured the surface fCO 2 in the northern East China Sea during four seasons; the spatial mean fCO 2 values were 311 ± 31 μatm in spring, 309 ± 53 μatm in summer, 376 ± 37 μatm in autumn, and 335 ± 17 μatm in winter. To identify the effects of lateral advection on the surface fCO 2 , the spatial mean surface fCO 2 values measured in the study area were compared with those in the East China Sea during four seasons (Table 1).…”
Section: Factors Influencing the Seasonal Variability Of Surface Fcomentioning
confidence: 99%
“…Prior studies have already revealed that the ECS is overall an annual net sink of atmospheric CO 2 , with significant seasonal variations (Chou et al, 2009;Chou et al, 2011;Kim et al, 2013;Peng et al, 1999;Shim et al, 2007;Tsunogai et al, 1999;Wang et al, 2000;Zhai and Dai, 2009). The ranges of present estimates are −3.3 to −6.5 in spring, −2.4 to −4.8 in summer, 0.4 to 2.9 in autumn and −13.7 to −10.4 mmol m −2 d −1 in winter.…”
Section: Introductionmentioning
confidence: 99%
“…The ranges of present estimates are −3.3 to −6.5 in spring, −2.4 to −4.8 in summer, 0.4 to 2.9 in autumn and −13.7 to −10.4 mmol m −2 d −1 in winter. However, these estimates are either based on limited (only one or a few) field surveys (Chou et al, 2009;Chou et al, 2011;Peng et al, 1999;Shim et al, 2007;Tsunogai et al, 1999;Wang et al, 2000) or suffer from spatial limitations (Kim et al, 2013;Shim et al, 2007;Tsunogai et al, 1999;Zhai and Dai, 2009). Tseng et al (2011) investigate the Changjiang diluted water induced CO 2 uptake in summer and obtain an empirical algorithm of surface water pCO 2 (partial pressure of CO 2 ) with the Changjiang discharge and sea surface temperature (SST).…”
Section: Introductionmentioning
confidence: 99%
“…The Yellow Sea Bottom Cold Water (YSBCW), which forms through winter cooling in the Yellow Sea, extends a considerable distance into the nECS (Lie 1984;Gong et al 1996). The atmospheric CO 2 sink (air to sea) during the summer in the nECS is significant (Wang et al 2000;Shim et al 2007;Kim et al 2013a). All of these processes suggest that the summer in this region is particularly dynamic due to both active physical mixing and biogeochemical processes.…”
Section: Introductionmentioning
confidence: 99%